ANALISIS KEBIJAKAN PENYERTAAN MODAL PEMERINTAH DAERAH TERHADAP KINERJA PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA PAREPARE - Nur, Muhammad (Economos : Jurnal Ekonomi dan Bisnis, 2020)
This study aims to find out how much the participation of the local government in PDAM Parepare City and to know the effect of the participation of the regional government capital on the performance of the Municipal Water Company (PDAM) of Parepare City. The data collection techniques used in this study are observation, interviews and documentation. Data analysis techniques in this study are using quantitative methods of financial performance formulas namely Current ratio, profit margin, operating ratio, return on investment (ROI). The results of this study indicate that the participation of local government capital to PDAM in general shows a value that continues to increase during the years 2014 - 2018 and the inclusion of regional government capital has no effect on PDAM performance.